#IBelieveHer: Representations of rape culture in Northern Ireland's media surrounding the 2018 Ulster Rugby Rape Trial. (1st September 2021) - McFalone, Kim
This article studies how Northern Ireland's media represented rape culture in relation to the 2018 Ulster Rugby Rape Trial. Thematic analysis was employed to analyse newspaper articles and social media posts to determine common themes surrounding the perpetuation of rape culture. While there were portrayals of perpetrator support and victim-blaming in the media, there was a surprising wealth of criticism surrounding the culture of misogyny, female subordination and sexual violence acceptance in Northern Ireland. This suggests Northern Irish society is becoming increasingly aware and intolerant of the damage rape culture acceptance can cause to all levels of society.